The Torah in 1 Maccabees : a literary critical approach to the text - Borchardt, Francis, 1981- (Deuterocanonical and cognate literature studies ;, 2014)
The significance of the ancestral norms for the Judean community depicted in 1Maccabees has never been thoroughly analyzed. This book takes up the debate concerning the composition of 1Maccabees and incorporates it into a discussion of the Judean ancestral traditions that seem most important to the Judean community it presents. This study sheds light on the complexity of opinions on Judean traditions by revealing the many voices in 1Maccabees.